ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR DI BEI - Chandra, Ellysya; Susanti, Merry (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research was conducted with the aim to test empirically the influence of leverage, leverage, cash flow, firm size, growth opportunity, and profitability on cash holding of manufacturing companies in the Indonesia Stock Exchange in 2017-2019. The sampling technique used purposive sampling method and data processing using Eviews 12 SV software. In this research, there were 33 companies as samples from 184 companies and were analysed by multiple linear regression. The results of this research indicate that, cash flow, firm size and profitability have a positive but not significant effect on cash holding, leverage has a negative and significant effect on cash holding, while growth opportunity has a negative but not significant effect on cash holding.